2022
DOI: 10.1364/optcon.441633
|View full text |Cite
|
Sign up to set email alerts
|

Parabolic microlensed optical fiber for coupling efficiency improvement in single mode fiber

Abstract: The efficiency of optical coupling between an optical fiber and other components be it a light source, a photodetector or another fiber, often depends on the performance of the focusing components. In optoelectronics, microlenses are generally incorporated at the end of optical fibers to ensure optimal coupling. These microlenses are primarily fabricated with a spherical profile easier to achieve, with a determined radius and at low production costs. However, these microlenses exhibit a relatively large waist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The larger experimental waist radius may be due to aspherical aberrations of the spherical lens surfaces. In a recent study on coupling efficiency improvement in single-mode optical fibers [12], the authors showed that imaging using a spherical lens surface on the optical fiber is strongly impaired by the aberration. As a consequence, the spot radius in the focal plane of a spherical lens may be up to three times larger than that of an aspheric lens surface with the same curvature radius at their apex as the spherical lens.…”
Section: Near-field Investigationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The larger experimental waist radius may be due to aspherical aberrations of the spherical lens surfaces. In a recent study on coupling efficiency improvement in single-mode optical fibers [12], the authors showed that imaging using a spherical lens surface on the optical fiber is strongly impaired by the aberration. As a consequence, the spot radius in the focal plane of a spherical lens may be up to three times larger than that of an aspheric lens surface with the same curvature radius at their apex as the spherical lens.…”
Section: Near-field Investigationsmentioning
confidence: 99%
“…Micro-scale refractive lens systems, where a lens is directly connected to the optical fiber, offer a great advantage with respect to compactness and efficiency and can be produced in different ways [3][4][5][6][7][8][9][10][11][12]. A very reliable and relatively simple fabrication of spherical end surfaces on silica fibers is achieved by using a commercial fiber splicer to control the shape of the fused fiber end, thus resulting in a ball lens section [6,7,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation